LGBTQ+ cardiovascular health equity: a brief review - Bonomo, Jason A.; Luo, Kate; Ramallo, Jorge A. (Frontiers in Cardiovascular Medicine, 2024)
Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in the United States. Data shows that social drivers of health (SDOH), including economic stability, racial/cultural identity, and community, have a significant impact on cardiovascular morbidity and mortality. LGBTQ+ (lesbian, gay, bisexual, transgender, queer, and other gender and sexual minority) patients face a variety of unique health risk factors and bear a disproportionate burden of CVD compared to cis-gender, heterosexual peers. There is a paucity of research assessing the etiologies of CVD health disparities within the LGBTQ+ community. Herein, we seek to explore existing literature on LGBTQ+ health disparities with a focus on cardiovascular disease, examine trends impacting LGBTQ+ health equity, and identify strategies and interventions that aim to promote LGBTQ+ cardiovascular health equity on a regional and national level.